COVID-19 outbreak and mitigation by movement restrictions : a mathematical assessment of economic impact on Nigerian households - Ayoade, Abayomi Ayotunde; Aliu, Oluwaseyi (Penerbit Universiti Kebangsaan Malaysia, 2022)
As COVID-19 continues to spread across the globe, governments all over the world have been finding ways of mitigating the pandemic. Various measures including lockdown and social distancing have been enacted to curb the spread of the virus. While the epidemiological trends of the disease have received considerable attention, the economic impacts of the outbreak on the households have been largely understudied. A compartmental model was developed and an epidemiological modelling approach was adopted to examine the economic impact of lockdown and social distancing on Nigerian households. The basic epidemiological features of the model were examined before the model was studied analytically and numerically. Both the analytical and numerical results showed that the economies of every household in Nigeria apart from the rich was badly affected by the mitigation measures of COVID-19 when there was an impediment to the payment of salaries and distribution of palliatives.